2017
DOI: 10.1038/nm.4418
|View full text |Cite
|
Sign up to set email alerts
|

Cytoplasmic p53 couples oncogene-driven glucose metabolism to apoptosis and is a therapeutic target in glioblastoma

Abstract: Cross-talk among oncogenic signaling and metabolic pathways may create opportunities for novel therapeutic strategies in cancer. Here we show that acute inhibition of EGFR-driven glucose metabolism induces minimal cell death, yet lowers the apoptotic threshold in a subset of patient-derived glioblastoma (GBM) cells. Mechanistic studies revealed that, following attenuated glucose consumption, Bcl-xL blocks cytoplasmic p53 from triggering intrinsic apoptosis. Consequently, pharmacological stabilization of p53 wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
67
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 88 publications
(68 citation statements)
references
References 53 publications
1
67
0
Order By: Relevance
“…Large-scale, shRNA library screening identified that the inhibition of MYC , P38MAPK , or ERK signaling pathways may be synthetically lethal with PI3K inhibitor PX-866 ( Kim et al, 2011 ). EGFR inhibition is synthetically lethal with pharmacological stabilization of P53 ( Mai et al, 2017 ). P53 mutations have also sensitized GBM cells to combined p-AKT inhibition and radiation by antagonizing DNA repair ( Palanichamy et al, 2018 ).…”
Section: Emerging Targets In Glioblastomamentioning
confidence: 99%
“…Large-scale, shRNA library screening identified that the inhibition of MYC , P38MAPK , or ERK signaling pathways may be synthetically lethal with PI3K inhibitor PX-866 ( Kim et al, 2011 ). EGFR inhibition is synthetically lethal with pharmacological stabilization of P53 ( Mai et al, 2017 ). P53 mutations have also sensitized GBM cells to combined p-AKT inhibition and radiation by antagonizing DNA repair ( Palanichamy et al, 2018 ).…”
Section: Emerging Targets In Glioblastomamentioning
confidence: 99%
“…Separate tumour cell lines have been found to respond differently to metabolism-altering compounds, with some eliciting heightened responses, due to their endogenous levels of hypoxia-induced factor 1-alpha (22). The PTEN status of cell lines has been shown to affect metabolic activity (23) as well as p53 (24). Potentially due to their mutant p53 alleles (25), the primarily glycolytic lines U251 and T98G have been shown to be unable to properly activate AMPK signalling (26) which is critical for survival in a hypoxic environment (27).…”
Section: Discussionmentioning
confidence: 99%
“…Following activation, it participates in various cellular processes such as cell senescence, apoptosis, DNA damage repair, cell cycle, antioxidative stress, energy metabolism regulation, tumor generation, and other physiological and pathological processes [38][39][40]. P53 plays a vital role in the apoptotic signaling pathways, including membrane apoptotic signaling and mitochondrial apoptotic pathways, and affects the transcription and expression of many apoptosis-related cytokines in the nucleus [41]. SIRT1 reduces the transcriptional activity of p53, and blocks p53-dependent cell apoptosis caused by DNA damage [42].…”
Section: Discussionmentioning
confidence: 99%